Analisa Pengaruh Perlakuan Panas Quench-Temper terhadap Nilai Kekerasan dan Kekuatan Tarik Baja JIS SUP 9 - Zainuri Anwar; Risky Irawan (Jurnal INOVATOR, 2021)
The raw material for making springs must have mechanical properties following the spring standards because the spring was receiving a dynamic load. This study aimed to improve the mechanical properties of the metal used as a material for making leaf springs. The material used is JIS SUP 9 steel which has a carbon content of 0.52-0.6%. The method used in this research is quenching and quench-tempering heat treatment. The used cooling medium was water, and the tempering temperature was at 300 °C. The mechanical properties of each specimen were tested by Vickers hardness and tensile test. The best heat treatment for material preparation is a quench-temper process, and the result was met with the manufacture of leaf spring. The findings explained that the hardness and tensile strength values were 504 HVN and 1555 N/mm2, respectively. This study could be a new insight for the leaf spring manufacture in the automotive industry.